2022
DOI: 10.3390/ani12243488
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Values of Industrial Hemp Byproducts for Dairy Cattle

Abstract: The objective of this experiment was to explore the nutritional components of industrial hemp byproducts (industrial hemp ethanol extraction byproduct, IHEEB; industrial hemp stalk, IHS; industrial hemp seed meal, IHSM; industrial hemp oil filter residue, IHOFR) and provide theoretical support for the application of industrial hemp byproducts in dairy cattle production. This experiment used a combination of a wet chemical method with Cornell Net Carbohydrate and Protein System, in situ nylon bag technique, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, different diet compositions and ruminal degradation characteristics may also be responsible for the lower VFA in dairy cows after ingestion of alternative diets. It has been suggested that IHEEB contains lower ruminal effective degradation rates compared to AH ( 51 ). Acetate and butyrate are precursors of milk fat synthesis ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different diet compositions and ruminal degradation characteristics may also be responsible for the lower VFA in dairy cows after ingestion of alternative diets. It has been suggested that IHEEB contains lower ruminal effective degradation rates compared to AH ( 51 ). Acetate and butyrate are precursors of milk fat synthesis ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, hemp extracts have been shown to be non-toxic to select non-target invertebrates [43,58] and may be beneficial to honeybee workers [59]. Hemp is also an emerging, readily cultivated crop in the U.S. [13,16,19,60] and its leaves are often discarded [33,57]. Thus, availability of raw material would not appear limited as it can be for other sources of biopesticides [46].…”
Section: Discussionmentioning
confidence: 99%
“…The hemp plant, Cannabis sativa, is a rapidly emerging high value specialty crop that can be cultivated for the production of a wide array of products [13]. For example, hemp seeds, which have numerous health benefits, are used to produce a diversity of goods including milk, dietary supplements, animal feed, and oil [14][15][16][17][18]. Furthermore, hemp bark and stems are used for industrial production of textiles, paper and even concrete [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional value of the feedstuffs was evaluated using the CNCPS system following the method of Wang et al [27]. The CNCPS divides the CP in the feed into nonprotein nitrogen (PA), rapidly degradable protein (PB1), moderately degradable protein (PB2), slowly degradable protein (PB3), and unavailable protein (PC).…”
Section: Protein and Carbohydrate Fractionsmentioning
confidence: 99%